How to bring the creation processes of the research to the writing? (Revista Apotheke, 2020)
This article was written by three researchers, who share the investigation on Creation Processes at the intersection among Art, Education and Research. It presents concepts on the Genetic Criticism by the professor Cecília Almeida Salles and three complementary narratives from each author, about the creation process of the writing, during the development of each individual research. On the weave of read, said, whispered, picked, drawn, sketched and written words on surfaces such as diaries, sketchbooks and colored pieces of paper on the walls, thoughts, reflection, wishes and discoveries materialize, which, gradually, enbody the text. By weaving approaches between creation and research, the authors invite the reflection they share: How to bring the creation processes of the research to the writing?
Keywords: creation process; art education; academic research